2020
DOI: 10.1097/cad.0000000000000997
|View full text |Cite
|
Sign up to set email alerts
|

3,3′-diindolylmethane exerts antiproliferation and apoptosis induction by TRAF2-p38 axis in gastric cancer

Abstract: 3,3′-diindolylmethane (DIM), an active phytochemical derivative extracted from cruciferous vegetables, possesses anticancer effects. However, the underlying anticancer mechanism of DIM in gastric cancer remains unknown. Tumor necrosis factor (TNF) receptor-associated factor 2 (TRAF2), one of the signal transduction proteins, plays critical role in proliferation and apoptosis of human gastric cancer cells, but there are still lack of practical pharmacological modulators for potential clinical application. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Similar to the results in human studies [6,57], we found that DIM induces autophagy in fission yeast (Fig. 4B) when we used the low concentration of DIM ( 5μg/ml).…”
Section: Mechanism Of Autophagy Induction By Dimsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to the results in human studies [6,57], we found that DIM induces autophagy in fission yeast (Fig. 4B) when we used the low concentration of DIM ( 5μg/ml).…”
Section: Mechanism Of Autophagy Induction By Dimsupporting
confidence: 88%
“…Recent studies in humans show that DIM is a potential anti-cancer drug that acts by the induction of apoptosis in a wide range of cancer types including the breast [11,12,52,56], prostate [16], gastric [57], pancreatic [58], and hepatoma [13].…”
Section: Dim Induces Apoptosis In Fission Yeastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in humans show that DIM is a potential anti-cancer drug that acts by the induction of apoptosis in a wide range of cancer types including the breast [11,12,52,57], prostate [16], gastric [58], pancreatic [59], and hepatoma [13]. DIM also induces autophagy that substantially suppresses tumor growth and causes cancer cell death [58,[60][61][62]. However, the mechanisms of autophagy and apoptosis induction by DIM in humans are not fully understood.…”
Section: Dim Induces Apoptosis In Fission Yeastsmentioning
confidence: 99%
“…Furthermore, the pro-apoptotic protein Bax and the ant-apoptotic protein Bcl2 are signs of apoptosis induction, which may be useful targets in the mitochondrial-dependent pathway of apoptosis [ 11 , 12 ]. Therefore, apoptosis induction in cancer cells can be used as a new weapon against cancer cell proliferation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%